NILAI-NILAI RELIGIUS DALAM NOVEL KEMBARA RINDU KARYA HABIBURRAHMAN ELSHIRAZY - Ngimadudin; Kasnadi; Munifah, Siti (STKIP PGRI Ponorogo Press, 2021)
Literary work is one of the interesting object to study. One of the popular literary works is novel. This study aims to describe the realization of religious values contained in the novel Kembara Rindu written by El-Shirazy. The method used in the study is descriptive qualitative, designed as literature review. The data are in the form of sentence or paragraph, taken from the object under study. Data collection is done by reading the object carefully and connected to the problem being analyzed. This study uses several stages of data processing techniques, starting from classification, analysis, evaluation, and conclusion step. Based on the research, the novel Kembara Rindu describes the values of religiosity through the form of: (i) the relationship between humans and God, (ii) the relationship between humans and humans, and (iii) the relationship between humans andthemselves.